Eksistensi dan Fungsi Kulkul pada Masyarakat Desa Bayung Gede, Kecamatan Kintamani, Bangli, Bali - Udayana, I Kadek Mustika; Sukardja, Putu (Humanis; Vol 19 No 1 (2017), 2017)
Kulkul is known as one of the traditional means of communication. Despite a fairly rapid development of technology, but kulkul a traditional means of communication can still survive to this day, especially in rural areas. Bayung Gede village has various types kulkul or the gong believed the community to help conduct activities within an organization in the village. The kulkul in the village Bayung Gede, namely: Kulkul pajenengan or Bulus, Kulkul Seka Gong and Baris, Kulkul Pengayah Istri, Kulkul Ida Ratu Gede Kanginang, Kulkul Krama Desa, and Kulkul Krama Pengayah. Each kulkul composed of various functions which are trusted and obeyed by people Bayung Gede. In this research, the end result of two existing problems: firstly the existence of kulkul at communities in Bayung Gede, in this case contains the definition of the existence of kulkul which still exist. Secondly, the funcyion of kulkul in society of Bayung Gede village in which describes the rules and the right procedures for the use of kulkul and restrictions for the public related to the use in any activities that will be implemented, in this case using functional theory of B. Malinowski. Malinnowski state that the function from the element culture is an ability to full fill some basic needs or some basic needs that appear from the basic needs, with the expected presence the kulkul at Bayung Gede village could survive and still exist even though the technology is now increasingly advanced.
Keywords: function, the existence of kulkul